SCENARIOS OF LOYALTY IN THE RELATIONS OF KABARDINIANS AND BALKARS WITH THE IMPERIAL ADMINISTRATION: SYMBOLISM, PRAGMATICS AND POLITICAL EFFECT - D. N. PRASOLOV (Кавказология, 2021)
The inclusion of Kabardinians and Balkars in the administrative and political space of the Russian Empire was accompanied by the formation in their political culture of public practices related to the expression of loyalty to the Romanov dynasty. Within the framework of military-popular administration one of the most widespread ways of registration of loyalty declarations were congress of entrusted of Great and Minor Kabarda and five mountain (Balkar) societies.  Based on archival documents and periodical press materials, the formation of the symbolic and practical component of the loyalty scenarios is examined. Its key symbols were the "people's banner", granted by Nicholas I in 1844, and historical examples, which emphasized the deep historical tradition of serving the Russian throne, starting from Ivan IV.  The practical side of loyalty implied regular confirmations of readiness to mobilize the human and financial resources of society. An analysis of the stories revealed a consistent pragmatism in the use of actions of loyalty to the throne for the favorable resolution of urgent social problems. Such an approach in relations with the imperial authorities has demonstrated a certain practical effectiveness. On May 21, 1889, Alexander III bestowed Kabardians and five mountain (Balkarian) societies of Zolsky and Gorny pastures under the condition of allegiance. Since August 25th, 1905 there was an administrative reunion of Great and Minor Kabarda in structure of Nalchiksky area.